2003
DOI: 10.1002/ijc.10980
|View full text |Cite
|
Sign up to set email alerts
|

Expression of peroxisome proliferator‐activated receptors (PPARs) in human urinary bladder carcinoma and growth inhibition by its agonists

Abstract: Recent studies have demonstrated that peroxisome proliferator activator-receptors(PPAR)-␥ is expressed in various

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 24 publications
2
69
1
4
Order By: Relevance
“…Very weak immunohistochemical staining of PPARg was shown in benign prostatic hyperplasia and normal prostate tissues, whereas significant enhancement in the expression of immunoreactive PPARg was observed in malignant prostate tissues (Park et al, 2001). PPARg expression was shown to be higher in high-grade bladder cancer compared to low-grade cancer (Yoshimura et al, 2003). Irrespective of the differentiation status of the tumour, strong expression of immunoreactive PPARg was observed in surgically resected human gastric cancer tissues (Sato et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Very weak immunohistochemical staining of PPARg was shown in benign prostatic hyperplasia and normal prostate tissues, whereas significant enhancement in the expression of immunoreactive PPARg was observed in malignant prostate tissues (Park et al, 2001). PPARg expression was shown to be higher in high-grade bladder cancer compared to low-grade cancer (Yoshimura et al, 2003). Irrespective of the differentiation status of the tumour, strong expression of immunoreactive PPARg was observed in surgically resected human gastric cancer tissues (Sato et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…It is expressed in high levels in different cancer including colon (Bull, 2003), breast , bladder (Yoshimura et al, 2003), prostate (Smith and Kantoff, 2002), head and neck (Jaeckel et al, 2001), cervical (Han et al, 2003) and endometrial cancer (Tong et al, 2000). Recent studies have demonstrated that ligand activation of PPARg receptor is involved in adipocyte (Seo et al, 2004) and tumour cell differentiation (Gauthier et al, 2003).…”
mentioning
confidence: 99%
“…Yoshimura et al 90 have reported a marked expression of PPARγ in bladder cancer tissue compared with normal bladder urothelium. Furthermore, higher levels of expression were associated with higher grade and advanced stage, suggesting that PPARγ agonists may mediate more potent anti-tumor effects in the more aggressive types of bladder cancer.…”
Section: Pparγ and Pparγ-agonists In Bladder Cancermentioning
confidence: 99%
“…In contrast, H-PGDS is a splenetic enzyme and is expressed in antigen-presenting dendritic cells as well as in mast cells of various organs 3) . Its product PGD 2 and one of its metabolites, cyclopentenone 15-deoxy-∆ 12, 14 -PGJ 2 (15d-PGJ 2 ), has been shown as a specific ligand of peroxisome proliferator-activated receptor γ (PPARγ) 4,5) and possess anti-neoplastic (anti-tumor) activity in human cancers of various organs 6,7,8,9,10,11) even no clinical application has carried out. Anti-tumor activity of 15d-PGJ 2 ( Fig.1) Repression of the TERT (Fig.1 ①) Telomerase reverse transcriptase (TERT) is known as a major determinant of telomerase activity and to be up-regulated in various cancer cells 12) .…”
mentioning
confidence: 99%
“…It has been reported that PPARγ has been shown to be expressed in many cancers, including pancreas, breast, lung, thyroid, prostate, and bladder, and has been demonstrated to potentially play an important role in carcinogenesis 18,19) . 15d-PGJ 2 , a ligand of PPARγ, have shown to inhibit tumor growth of the cells in various organs tumors such as stomach 6) , colon 7) , lung 8) , breast 9) , bone marrow 10) and bladder 11) .…”
mentioning
confidence: 99%